Analisis Antarmuka Pengguna Aplikasi PeduliLindungi untuk Meningkatkan Pengalaman Pengguna dengan Metode Evaluasi Heuristik: - - Andry, Johanes Fernandes; Clara, Monica; Chandra, William; Antonio, Marco; Bernanda, Devi Yurisca (UIR PRESS, 2024)
The Covid-19 pandemic limits human activities every day. The spread of the virus is uncontrollable, it can attack anyone, anytime, and anywhere. As a solution, the use of the PeduliLindungi application technology developed by the Ministry of Communication and Information in collaboration with other relevant Ministries and Institutions is used to help track the spread of viruses and understand preventive measures to stop their spread. Research was conducted on the appearance of the application's User Interface using the Heuristic Evaluation method to measure its usefulness. However, there are several problems experienced by users, namely the information is not updated (vaccines and Covid-19 tests), the language used is inconsistent, and others. Questionnaire testing with 10 questions based on 10 Heuristic Evaluation criteria was distributed via Google Form to 33 respondents. Then, carry out validity and reliability tests with the research results obtained Valid and Reliable. as well as testing the hypothesis of all Learnability, Efficiency, Memorability, and Error Prevention factors, based on usability and user satisfaction aspects, questionnaire items all test results are accepted and there are no serious problems. However, there are a number of things that need to be improved so that the application can run more optimally.